Differences of Spermatozoa Concentration Analysis Between Manual and Automatic Methods - Emma Ismawatie; Purwanto Adhipireno; Seso Sulijaya Suyono; Edy Purwanto; Budi Santoso; Edward Kurnia Setiawan Limijadi (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2021)
The examination of sperm concentration in the laboratory is the calculation of the number and motility using a microscope or using a device. There are still some clinicians who doubt the accuracy of the sperm count results using a semen analyzer rather than using the manual method. This study aims is to determine the differences of the sperm concentration examination between the manual method and the automatic method. Subjects in this study were patients who carried out semen analysis tests at the Clinical Pathology Laboratory of RSIA "Restu Ibu" Sragen from June to August 2020. The object of this research is the examination of sperm concentration, using a manual method using a hemocytometer and an automatic method using the LensHooke ™ SQA X1 Pro. The results of statistical tests using the Mann Whitney methods show that the significance value (p) was 0.960, which means that there was no difference in the results of  the sperm concentration examination between the manual method and the automatic method. Result of this research shows that there is no weakness or significant difference if compared between manual and automatic methods.